2020
DOI: 10.1002/wer.1354
|View full text |Cite
|
Sign up to set email alerts
|

Operational and structural A‐stage improvements for high‐rate carbon removal

Abstract: Biosorption of organics is investigated at two sites in order to optimize operation and infrastructure for carbon removal and redirection in upstream, high‐rate processes. Sufficient process temperature and stable mixed liquor solids concentration were established as the key impact parameters for the process performance. Improved COD removal was achieved by either substantially enhanced aeration (elevated metabolic state) or by enhanced flocculation capability (dosed chemicals). Separation and thickening of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The quality of the effluent obtained in this study with the HR-MBR was much higher than that found with other competitive technology for carbon recovery from municipal wastewater. It has been reported that HRAS systems (A-stage systems) can achieve a COD removal rate of 52–64% [ 27 , 28 ]. As another emerging technology for carbon capture, direct membrane filtration (DMF) (in which no biological treatment is promoted) could not produce treated water with a low concentration of COD (<30 mg/L) without using coagulation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the effluent obtained in this study with the HR-MBR was much higher than that found with other competitive technology for carbon recovery from municipal wastewater. It has been reported that HRAS systems (A-stage systems) can achieve a COD removal rate of 52–64% [ 27 , 28 ]. As another emerging technology for carbon capture, direct membrane filtration (DMF) (in which no biological treatment is promoted) could not produce treated water with a low concentration of COD (<30 mg/L) without using coagulation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…This issue can be mitigated by shifting to an AAA™ (Alternated Activated Adsorption) process. AAA is a retrofitted primary clarifier which acts as primary settler and A-stage combined in one tank where the feed is introduced through the settled sludge bed (Wett et al, 2020).…”
Section: Technology Solutions To Manage Capture Of Fines and Optimize...mentioning
confidence: 99%
“…Most conventional facilities have a "primary process" with clarifiers applying gravitational forces for removal of organics exclusively in form of total suspended solids. Our value proposition is to enhance the primary treatment step to an alternating activated adsorption (AAA) settler instead to (1) make better use of this infrastructure within the existing hydraulic profile, (2) intensify the biological step, (3) use less energy in the biological step, (4) produce more gas in a digester, (5) produce 5% thickened solids, and (6) replace cumbersome primary mechanical equipment such as chains and flights with air lift sludge withdrawal (Wett, Aichinger, Hell, et al, 2020). Hence, the goal of the AAA settler is to convert a portion of influent soluble COD and ammonia through assimilatory means to particulate heterotrophs and to a protein extracellular polymeric substances (EPS) matrix (Homyok et al, 2024), in a very compact design (0.5 days solids residence time and 2 h hydraulic retention time) to achieve both carbon and nitrogen redirection.…”
Section: Introductionmentioning
confidence: 99%